(untitled) (Semiárida, 2020)
During the growing season of 1988/89 a trial was held in the large vegetable experimental field at the Agronomy Faculty of the University of La Pampa, under square latin design 5 x 5. Fertilizers of N, P and S were applied to the Synthetical Variety 14 of Valenciana onion. The main objective was to determine the influence of N and its interaction of P and S upon final yield. The fertilizars were: Urea; H(NH4)2 PO4 + Urea; (NH4)2 SO4 +Urea; (NH4)2 SO4 +H(NH4)2 PO4 +Urea and tester. All doses were adjust in such manner all plots had the same amount on N, in order to compare its effects. Highly significantive differences were observed between treatments. With respect to entire plant’s weight expose to the air, T2 overcame significantly to Tc and T1. Calcium, Magnesium, phosphorus, crude protein and water contens were analyzed in lab and the results are considered normal. According to the results obtained in the current trial, it might be suggested to fertilize onion with compounds including N and Pinto their composition.